Reproductive Interference and Niche Partitioning in Aphidophagous Insects - Suzuki Noriyuki; Naoya Osawa (Psyche: A Journal of Entomology)
The range and quality of prey species differ greatly among closely related species of predators. However, the factors responsible for this diversified niche utilization are unclear. This is because the predation and resource competition do not always prevent species coexistence. In this paper, we present evidence in support of reproductive interference as a driver of niche partitioning, focusing on aphidophagous insect. Firstly, we present closely related generalist and specialist species pairs in aphidophagous lacewings to compare the reproductive interference hypothesis with two other hypotheses that have been proposed to explain niche partitioning in lacewings and sympatric speciation through host race formation and sexual selection. Secondly, we present a case study that shows how reproductive interference can drive niche partitioning in sibling ladybird species. Thirdly, we show that many ladybird genera include species inhabiting the same region but having different food and habitat preferences, raising the possibility that reproductive interference might occur in these groups. Finally, we show that intraguild predation cannot always explain the niche partitioning in aphidophagous insects including hoverflies and parasitoids. On the basis of the evidence presented, we urge that future studies investigating predator communities should take account of the role of reproductive interference.